Isolasi Methicillin Resistant Staphylococcus aureus pada Mikrofon yang Digunakan saat Aktivitas Perkuliahan di Fakultas Kedokteran dan Ilmu Kesehatan Ukrida - Donna Mesina Pasaribu; Amelia Graciella Tjiptabudy; Kris Herawan Timotius (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Microphone is an audio tool that is generally used during lecture. Microphone is not only used by one individual, but also by many people, a potential source of bacterial spread. The purpose of this study was to determine the presence or absence of Methicillin Resistant Staphylococcus aureus in the microphones used at the Faculty of Medicine and Health Sciences, Krida Wacana Christian University (FKIK UKRIDA). Research was conducted by using a descriptive study method with a total sampling technique. Samples taken in 2019 were all microphones used in the lecture process at the FKIK UKRIDA. A total of 26 microphones were examined by means of performing a swab on each microphone and planted on mannitol salt agar media, then transferred to nutrient agar. It was then followed by a catalase testing, gram staining, mannitol sugar testing, and sensitivity test of Staphylococcus aureus bacteria against oxacillin antibiotics. Results showed that 11 microphones contained Staphylococcus aureus bacteria and, on the sensitivity test results, all bacteria grown were sensitive to oxacillin antibiotics. The study concludes that no Methicillin Resistant Staphylococcus aureus found on the microphones used during lecture activities in FKIK UKRIDA.